The Right to Inhabit. Reflection on Forced Displacement and Social Movements. - Sánchez Estévez, Reyna (Geografares, 2017)
This paper exposes initial data from an investigation into the protests and social struggles against forced displacement of people from Mexico, it is given to know the places where protests are developed, the reasons which originate them and the characteristics of the participant subjects, a first analysis of the resistance objectives is also done and some elements of their repertoires of protest are offered. A reflection on the damage caused by these displacements in human beings and on the notions of risk and vulnerability is made. Keywords: Social movements, evictions, vulnerability.